2004
DOI: 10.1074/jbc.m408997200
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine γ-Lyase Overexpression Inhibits Cell Proliferation via a H2S-dependent Modulation of ERK1/2 Phosphorylation and p21Cip/WAK-1

Abstract: Cystathionine ␥-lyase (CSE) is a key enzyme in the trans-sulfuration pathway. CSE uses L-cysteine as a substrate to produce hydrogen sulfide (H 2 S). The CSE/H 2 S system has been shown to play an important role in regulating cellular functions in different systems. In the present study, we used CSE stably overexpressed HEK-293 cells to explore the effect of the CSE/H 2 S system on cell growth and proliferation. The overexpression of CSE resulted in increases in CSE mRNA levels, CSE proteins, and intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 36 publications
6
118
0
2
Order By: Relevance
“…generated and exogenous H 2 S can inhibit cell proliferation. 21 Accordingly, our data show that sulfur ions inhibit p38 MAPK phosphorylation, which is relevant in inducing apoptosis in neutrophils, as pharmacological inhibition of p38 by SB202190 efficiently inhibits apoptosis to the same extent as HS À ions. Moreover, surviving neutrophils show efficient bactericidal properties, which adds clear physiological relevance to their prolonged survival.…”
Section: Discussionmentioning
confidence: 93%
“…generated and exogenous H 2 S can inhibit cell proliferation. 21 Accordingly, our data show that sulfur ions inhibit p38 MAPK phosphorylation, which is relevant in inducing apoptosis in neutrophils, as pharmacological inhibition of p38 by SB202190 efficiently inhibits apoptosis to the same extent as HS À ions. Moreover, surviving neutrophils show efficient bactericidal properties, which adds clear physiological relevance to their prolonged survival.…”
Section: Discussionmentioning
confidence: 93%
“…From the functional point of view, in agreement with data from other groups, [35][36][37] MEK inhibition (by U0126) suggested that the MEK-ERK signaling has a major role in the control of NCTC cell proliferation. The antiproliferative effects of NaHS are now well documented at least in lymphocytes in vitro [38][39] and in smooth 41 and to increased c-Jun, Raf, MAPKK, MEK and ERK mRNA expression levels in IEC-18 rat intestinal cells. 15 The effects of sulfurs on keratinocytes, however, seem more complex, as the role of several survival/ proliferation pathways produce different effects on adherent or nonadherent cells: (i) neither inhibition of ERKs nor p38 activation is sufficient to reduce cell viability of nonadherent NCTC cells or to interfere with their adhesion, however, U0126 increases cell death of NaHS-treated adherent cells; (ii) sulfurs do not modulate the PI3K pathway in NCTC cells, however, LY294002 abolished colony formation, reduced S phase and partially prevented cell death of NaHS-treated adherent NCTC.…”
Section: H2s Downregulates Erk In Keratinocytesmentioning
confidence: 99%
“…Relative mRNA quantification was calculated by using the arithmetic formula '2 ÀDDC T ', where DC T is the difference between the threshold cycle of a given target cDNA and an endogenous reference cDNA. 9,22,23 Thus, this value yields the amount of the target normalized to the endogenous reference of b-actin.…”
Section: Measurements Of Pancreatic Islet H 2 S Production and Insulimentioning
confidence: 99%
“…[3][4][5] Altered cell proliferation or apoptosis induced by H 2 S has also been widely reported. [6][7][8][9][10] Endogenous production and physiological function of H 2 S in pancreas have been studied with identification of both CBS and CSE in rat pancreatic tissues or cloned rat pancreatic b-cell line. 11,12 In recent years, pathophysiological implications of the CSE/H 2 S system in diabetes have been reported.…”
mentioning
confidence: 99%